(untitled) (Revista Rupturas, 2023)
A discussion is offered on how neoliberal subjectivity is produced under an economic idealism, of the market and of individual freedom. Premises show that neoliberalism is not only a practice in the economic field but also a loss of a social project and individualization in the psychological plane that requires each person to face reality in isolation and where each one can reach/buy individually what is necessary. The idea of entrepreneurship is explained as one of the neoliberal strategies to individualize and delegitimize the need for States. It is a theoretical reflection that analyzes historical contextual data from Costa Rica and El Salvador, government plans, policies already applied, bills, public discussions and journalistic notes.